Story: substance, structure, style, and the principles of screenwriting - McKee, Robert (New York: Harper-Collins Publishers, 1997)
Contents: The winter and the art of story. The elements of story. The principles of story design. The writer at work.
Includes bibliographical references and index
Keywords: Motion picture autorship